TRANSGENDERISM, SOCIETAL DYSPHORIA, AND RESTORATION OF THEIR SOCIAL PRESTIGE. - Dr. Muhammad Yaseen; Dr. Muhammad Imran; Dr. Ammara Rehman; Humaira Khalil; Farzana Iqbal; Dr. Muhammad Ayaz (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Allah has not only created human beings but also raised their status. As Holy Quran says ???????? ?????????? ????? ????? and ?????? ????????? ??????????? ??? ???????? ????????? . Modern days Muslims have forgotten these sayings of Almighty and divided the people into two categories according to their own will. Born in normal. Born in abnormalities. The second type of people are called by different names i.e., Khunsa, Hejira, Transgender, Transsexual, and Intersex, etc. They are commonly called 3rd gender. They are humiliated in every society especially in 3rd world countries. Wherever they are seen, people give mocking gestures. The youngsters and children follow them and pass derogatory remarks for them. They are also considered sexual phenomena. The question arises in the minds of sensible people, what are their faults if they are created in this stature. It is the will of Allah, the Creator who creates them according to His Will. These people are facing insulting behavior from the people. Their families are not ready to accommodate them. They are not able to get jobs or houses on rent. They are forced to live in their communities, where they are forced to follow the commands of their gurus in order to earn bread and butter and shelter. Even they are forced to beg and involve in sexual activities to live. As a result, the localities, they are living, are suffering from aids and other fatal diseases. In modern days medical inventions have brought a revolution in every field. The diseases which were never cured are now treated effectively. People who are born in the wrong bodies can be treated by hormones therapy and sex-change surgery. Resultantly, they can be able to live a respectable life in society. This paper discusses; How sex is determined? societal behaviors with Trans genders, The behavior of the prophet (PBUH) with trans genders, the available treatments, advantages of sex change.